A new uterine endometrium preservation hysteroscopic myomectomy: Introduction of improved procedures and a retrospective analysis of 94 cases - Wataru Isono; Masanori Maruyama (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Objective: To reduce the damage of uterine endometrium caused during hysteroscopic myomectomy (HM) for reproductive aged patients, a new uterine endometrium preservation hysteroscopic myomectomy (UEP-HM) has been developed. In this study, we introduced this technique with comparing to the conventional hysteroscopic myomectomy (C-HM). Study Design: The data from 94 patients aged 42 or younger who underwent HM (38 cases with UEP-HM and 56 cases with C-HM) for treating single Type 1 or Type 2 submucosal leiomyoma (SL) were analysed retrospectively for comparing the characteristics of both patient and target SL. In this process, we defined the operation time 60 min or over as the longtime operation (LTO) and the SM sized 3 cm or over as the large submucosal leiomyoma (LSL) for detecting the influential factors, including this procedure, on the difficulty of HM. For assisting the prediction of operation time (OT), we investigated the relationship between the OT and the cube of average diameter (AD) of target SL referring with some past reports. Results: Although when comparing UEP and control groups, parity, AD, the number of patients with Type 2 SL, OT, and the number of infertile patients showed significant difference, in the multivariate analysis only LSL showed the significant influence on the possibility of LTO. Next, we compared OT/Cube of AD, which calculated by dividing OT by the cube of AD for evaluating OT from the target SL size and confirmed that there was no difference in those 2 groups (3.7 ± 3.0 (95 %CI: 0.9 - 13.3, n = 38) vs. 3.9 ± 3.2 (95 %CI: 0.4 - 17.3, n = 56), p = 0.79). Conclusions: The new UEP-HM can become an alternative method of C-HM without procedure-specific difficulty. In the future, to investigate the prognosis of this procedure, more patients and further analyses should be accumulated.